A Core Outcome Set for Trials in Glomerular Disease: A Report of the Standardized Outcomes in Nephrology–Glomerular Disease (SONG-GD) Stakeholder Workshops. Issue 1 (January 2022) - Carter, Simon A.; Lightstone, Liz; Cattran, Dan; Tong, Allison; Bagga, Arvind; Barbour, Sean J.; Barratt, Jonathan; Boletis, John; Caster, Dawn J.; Coppo, Rosanna; Fervenza, Fernando C.; Floege, Jürgen; et al.
Visual Abstract: Abstract : Background and objectives: Outcomes reported in trials in adults with glomerular disease are often selected with minimal patient input, are heterogeneous, and may not be relevant for clinical decision making. The Standardized Outcomes in Nephrology–Glomerular Disease (SONG-GD) initiative aimed to establish a core outcome set to help ensure that outcomes of critical importance to patients, care partners, and clinicians are consistently reported. Design, setting, participants, and measurements: We convened two 1.5-hour workshops in Melbourne, Australia, and Washington, DC, United States. Attendees were identified purposively with 50 patients/care partners and 88 health professionals from 19 countries; 51% were female. Patients and care partners were from the United States, Australia, and Canada, and had experience of a glomerular disease with systemic features ( n =9), kidney-limited nephrotic disease ( n =9), or other kidney-limited glomerular disease ( n =8). Attendees reviewed the results of the SONG-GD Delphi survey and aims of the workshop and then discussed potential core outcomes and their implementation in trials among moderated breakout groups of eight to 12 people from diverse backgrounds. Transcripts of discussions were analyzed thematically. Results: Three themes were identified that supported the proposed core outcomes: limiting disease progression, stability and control, and ensuring universal relevance ( i.e., applicable across diverse populations and settings). The fourth theme, preparedness for implementation, included engaging with funders and regulators, establishing reliable and validated measures, and leveraging existing endorsements for patient-reported outcomes. Conclusions: Workshop themes demonstrated support for kidney function, disease activity, death, life participation, and cardiovascular disease, and these were established as the core outcomes for trials in adults with glomerular disease. Future work is needed to establish the core measures for each domain, with funders and regulators central to the uptake of the core outcome set in trials.